Carcinomatous encephalitis as clinical presentation of occult lung adenocarcinoma: case report - Ribeiro,Henrique Barbosa (2007)
Carcinomatous encephalitis is a rare entity, originally described by Madow and Alpers in 1951, which is characterized by tumoral spreading perivascular, without mass effect. Clinical manifestations such as hemiparesis, seizures, ataxia, speech difficulties, cerebrospinal fluid findings as well as computed tomography are nonspecific. This leads the physician to pursue more frequent diseases that could explain those manifestations - toxic, metabolic, and/or infectious encephalopathy. A magnetic resonance imaging (MRI) with gadolinium, the method of choice, presumes the diagnosis. Previous reports of this unusual form of metastatic disease have described patients with prior diagnosis of pulmonary adenocarcinoma. We present the case of carcinomatous encephalitis in a 76-years-old woman as the primary manifestation of occult pulmonary adenocarcinoma with its clinical, imaging, and anatomopathological findings.